1992
DOI: 10.1111/j.1752-7325.1992.tb02280.x
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of Dentists on the Treatment of Elderly Patients in Long‐term Care Facilities

Abstract: The high prevalence of disorders in the mouths of elderly residents in long-term care (LTC) facilities suggests that the dental services available to the residents are inadequate. A questionnaire was sent to most of the dentists practicing in Vancouver (British Columbia) to solicit their opinions on treating older patients in LTC facilities, and a response was obtained from 334 (55%). It indicated that 19 percent of the respondents had treated old people within this context, although few of them felt they had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 13 publications
(5 reference statements)
3
74
0
Order By: Relevance
“…The practical barriers expressed by the participants are in accordance with what was found in the studies carried out among dentists working in a long‐term care facility by MacEntee et al ,. Weiss et al .…”
Section: Discussionsupporting
confidence: 86%
“…The practical barriers expressed by the participants are in accordance with what was found in the studies carried out among dentists working in a long‐term care facility by MacEntee et al ,. Weiss et al .…”
Section: Discussionsupporting
confidence: 86%
“…12 A number of significant barriers to the provision of adequate dental care for residents of aged care facilities have been identified by dentists and RACF staff, particularly the lack of portable equipment, difficult working conditions in RACFs, apathy of residents and staff, uncooperative administrators, residents' behavioural and communication problems and perceived lack of training in geriatric dentistry. 11,[13][14][15][16][17] Financial considerations are also known to affect the decision to provide treatment for residents. Carers often have limited knowledge and education in oral hygiene care and dental disease, and this impacts on their ability to provide adequate care to residents.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, a great majority of the participants were low‐income older adults or those with special‐needs. Evidence showed that, because of the lack of resources for dental care, physical or mental disability, lack of social support and transportation, neglect, and other reasons, older adults with special needs have more difficulties accessing necessary dental care than their healthy, independent counterparts 30–36 . In this circumstance, although number of teeth with restorations indicates past history of dental caries, to some degree, it also reflects the ability of an older adult with special needs to obtain necessary dental care, including treatment of caries.…”
Section: Discussionmentioning
confidence: 99%